(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Language has a powerful influence over people and their behaviour. This is especially true in the fields of marketing and advertising. The choice of language to convey specific messages with the intention of influencing people is vitally important. This paper attempts a contrastive analysis of the language of advertising (traditional buying and selling) in Ibibio and a variety of Nigerian English, known by Jowitt (1991) as Popular Nigerian English (PNE). To carry out this investigation, the researcher relies on surreptitious tape recordings and his deep knowledge of marketing activities and its language in Ibibio. The paper discovers that while both languages have almost the same marketing schematic structure, the language of advertising is slightly different. The users of Ibibio employ a richer linguistic content in advertising, as the language is theirs and so the innuendos, persuasive and rhetorical devices are easily expressed. PNE though a variety of English that has been ‘accultured’ to carry the Nigerian experience, still poses a problem to some of its users resulting in frequent code-mixing, code-switching and interference. This research is concluded with the recommendations that language experts and the Nigerian government alike revisit the clamour (by the Nigerian people) for a national language that can suitably detail or express succinctly the collective Nigerian experience. The paper equally suggests that discourse analysts and language experts discourage the use of restructured English loan words in place of Ibibio equivalents by promoting the proper use of Ibibio.